A Simple Explanation on The Nobility of Gold Comparing to Other Metals: A First-Principles Study - Kristianto, Eduardus Oldi; Masan, Samuel Eka Putra Payong; Prabowo, Wahyu Aji Eko; Rusydi, Febdian; Iqbal, Muhammad; Irzaman; Nugroho, Widagdo Sri (International Journal of Integrated Engineering, 2022)
We tested the reactivity of an Au surface against H2 and compared the reactivity with Ag, Cu, and Pt surfaces. The reactivity is represented by the H2 dissociation energy over each surface. Their dissociation energies were calculated based on DFT calculation with PBE functional and PAW pseudopotential. The calculation results show that the Pt surface is the most reactive, followed by the Cu, Ag, and Au surfaces. PDOS illustrates the d-band center is above Fermi level only on the Pt surface which indicates that it is the most reactive towards H2. While the adsorbate charge shows that Cu donates the most electrons, trailed by Ag and Au. This review concludes that Au surface is the most inert among the other three metals. This inertness is a characteristic that defines a noble metal.